European Union Energy Policy in the 21st Century: A Process of Riskification - Dekeyrel, Simon (2023)
In the 1990s, the European Union (EU) took the first important steps towards a common energy policy. Aided by the extraordinarily favourable environment of the end of the Cold War, it developed an energy policy around a model heavily inspired by the fundamental principles of European integration laid down in the Treaty of Rome in 1957, centred on the use of regulatory tools to build and maintain competitive markets.